Inkonsistensi Regulasi UU No. 1 Tahun 2013 Dalam Implementasi dan Fakta Lapangan: Studi di Dua Lembaga KSPPS/BMT - Firda Aulia; Nadya Faizatur Rahmah; Hakam Ar Rasyid; Fatia Ismi Nabila; Cahya Wulandari; Fajriyatun Nurul 'Aini; Ainul Yaqin (J-Alif : Jurnal Penelitian Hukum Ekonomi Syariah dan Budaya Islam, 2026)
This study analyzes the regulatory inconsistency between Law Number 1 of 2013 on Microfinance Institutions and the institutional reality of Baitul Maal wat Tamwil (BMT). The law provides BMT with the option to operate as a Limited Liability Company or Cooperative, subject to OJK licensing and supervision. In practice, however, the majority of BMTs retain their status as Sharia Savings and Financing Cooperatives (KSPPS) under Law No. 25 of 1992, supervised by the Cooperative Agency, creating an initial gap in legal implementation. This non-compliance reflects not a regulatory failure, but a rational institutional choice as explained by Williamson’s Institutional Choice Theory. BMTs avoid the LKM/PT structure due to disproportionate OJK compliance costs including capital requirements, GCG standards, and reporting obligations relative to their operational scale. The result is a structural problem of overlapping and absent supervision, weakening risk management and consumer protection. This study recommends policy reformulation through structured regulatory coordination and a tiered supervision model, balancing prudential demands while preserving BMT’s identity as a community-based economic institution. Consumer protection should be strengthened through periodic sharia audits conducted by the Cooperative Agency in collaboration with DSN, and the establishment of a dedicated deposit guarantee institution for BMTs.